JENIS HIDROPONIK STATIS DAN LEVEL KONSENTRASI HUETT’S LETTUCE TERHADAP PERTUMBUHAN DAN PRODUKSI SELADA - zasari, maera; Saputra, Herry Marta; Aini, Sitti Nurul; Anisa, Novitra (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
Lettuce is a type of vegetable that is produced in a hydroponic system, one of which is a static hydroponic system. Hydroponic lettuce production usually uses a certain level of concentration. This study aims to determine the effect of the hydroponic system, concentration levels, and their interactions on the growth and yield of lettuce. The research was carried out in the research and experimental garden of the Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, using a factorial randomized block experimental design including a static hydroponic system and various concentrations of Huett's lettuce formulation, repeated 3 times. The results showed that the kratky hydroponic system was the best treatment. The concentration level of 500 ppm showed the highest mean yield. The combination of kratky hydroponic system treatment with a concentration of 500 ppm showed the highest average yield on the growth and yield of lettuce.